2000
DOI: 10.1021/jp000785v
|View full text |Cite
|
Sign up to set email alerts
|

Ab Initio and Density Functional Calculations of19F NMR Chemical Shifts for Models of Carbonic Anhydrase Inhibitors

Abstract: Ab initio (HF) and density functional theory (DFT) calculations of 19 F NMR chemical shifts were performed for models of fluoroaromatic inhibitors of carbonic anhydrase II (CA). DFT gave slightly better agreement with the experimentally measured chemical shifts of the actual inhibitors, suggesting that intramolecular dispersion does contribute significantly to the chemical shifts in these molecules. HF and DFT calculations for the stacked complex of hexafluorobenzene with benzene gave excellent agreement with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 63 publications
1
13
0
Order By: Relevance
“…4A) suggests that the ortho-F atom is approximately 4.5 Å from the phenyl ring of Phe16. Previous ab initio and density functional theory calculations of 19 F NMR shielding contributions from a benzene ring positioned near hexafluorobenzene, however, reported negligible shielding contributions at separation distances greater than 4.0 Å (27). Thus, ring current effects from Phe16 are not expected to contribute significantly to chemical shift differences of the fluorine nucleus in Tyr16Phe versus Tyr16Ser.…”
Section: Resultsmentioning
confidence: 84%
“…4A) suggests that the ortho-F atom is approximately 4.5 Å from the phenyl ring of Phe16. Previous ab initio and density functional theory calculations of 19 F NMR shielding contributions from a benzene ring positioned near hexafluorobenzene, however, reported negligible shielding contributions at separation distances greater than 4.0 Å (27). Thus, ring current effects from Phe16 are not expected to contribute significantly to chemical shift differences of the fluorine nucleus in Tyr16Phe versus Tyr16Ser.…”
Section: Resultsmentioning
confidence: 84%
“…Reasons for use of these methods were both our trial calculations for 19 F nuclei and previous reported calculations by other researches. In recent years, several groups have reported an excellent correlation and good agreement with experimental data using acceptable basis sets for 19 F‐NMR properties (31–35). All the studied molecules with the experimental values were collected in Table 3.…”
Section: Methods and Computational Detailsmentioning
confidence: 78%
“…Some early computational work (aimed at benchmarking and validation) included F 2 as test molecule, which proved to be challenging [26][27][28]. Interest in modeling 19 F shifts has steadily continued, and several papers have appeared in the last decade aimed at general structural issues, solution chemistry and physical organic chemistry, [29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46] solid-state issues (especially the prediction of chemical shift tensors), [47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64] J-couplings [65][66][67][68][69][70][71][72]…”
Section: Introductionmentioning
confidence: 99%